Implementation of E-Learning Program in IT Companies in Malaysia - A Study on Prudential Services - Francis V., Stephanie Sangeetha (2010)
The scope of this research is confined to IT organizations in Malaysia and the factors that can lead towards a successful implementation of e-learning in these companies. The objectives of this paper are to identify the factors that will contribute towards a successful implementation of e-learning in an IT company in Malaysia and to build and test model to measure the successful implementation.